Fibroblast activation protein alpha is expressed by transformed and stromal cells and is associated with mesenchymal features in glioblastoma - Busek, Petr; Balaziova, Eva; Matrasova, Ivana; Hilser, Marek; Tomas, Robert; Syrucek, Martin; Zemanova, Zuzana; Krepela, Evzen; Belacek, Jaromir; Sedo, Aleksi (Tumour biology, 2016)
Glioblastomas are deadly neoplasms resistant to current treatment modalities. Fibroblast activation protein (FAP) is a protease which is not expressed in most of the normal adult tissues but is characteristically present in the stroma of extracranial malignancies. FAP is considered a potential therapeutic target and is associated with a worse patient outcome in some cancers. The FAP localization in the glioma microenvironment and its relation to patient survival are unknown. By analyzing 56 gliomas and 15 non-tumorous brain samples, we demonstrate increased FAP expression in a subgroup of high-grade gliomas, in particular on the protein level. FAP expression was most elevated in the mesenchymal subtype of glioblastoma. It was neither associated with glioblastoma patient survival in our patient cohort nor in publicly available datasets. FAP was expressed in both transformed and stromal cells; the latter were frequently localized around dysplastic blood vessels and commonly expressed mesenchymal markers. In a mouse xenotransplantation model, FAP was expressed in glioma cells in a subgroup of tumors that typically did not express the astrocytic marker GFAP. Endogenous FAP was frequently upregulated and part of the FAP+ host cells coexpressed the CXCR4 chemokine receptor. In summary, FAP is expressed by several constituents of the glioblastoma microenvironment, including stromal non-malignant mesenchymal cells recruited to and/or activated in response to glioma growth. The limited expression of FAP in healthy tissues together with its presence in both transformed and stromal cells suggests that FAP may be a candidate target for specific delivery of therapeutic agents in glioblastoma.
Keywords: glioblastom; Cell Line, Transformed; transformované buněčné linie; RNA, Messenger; Male; fibroblasty; buňky stromatu; Endopeptidases; Gelatinases; Mesoderm; kvantitativní polymerázová řetězová reakce; Survival Rate; Fibroblasts; Cell Proliferation; následné studie; western blotting; prognóza; Neoplasm Staging; Seprase; membránové proteiny; Xenograft Model Antitumor Assays; Membrane Proteins; Adult; Stromal Cells; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; Real-Time Polymerase Chain Reaction; Follow-Up Studies; Glioma; myši inbrední NOD; xenogenní modely - testy protinádorové aktivity; Serine protease; Blotting, Western; Stromal cells; Animals; lidé; ženské pohlaví; studie případů a kontrol; Biomarkers, Tumor; Serine Endopeptidases; Humans; Glioblastoma; zvířata; serinové endopeptidasy; endopeptidasy; myši; nádorové buňky kultivované; apoptóza; Immunoenzyme Techniques; proliferace buněk; Prognosis; Reverse Transcriptase Polymerase Chain Reaction; Fibroblast activation protein α; mezoderm; Tumor Cells, Cultured; Mice; Female; Mice, Inbred NOD; imunoenzymatické techniky; lidé středního věku; staging nádorů; nádorové biomarkery; Apoptosis; míra přežití; Middle Aged; želatinasy